2012
DOI: 10.1007/s00382-012-1358-4
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the global lorenz energy cycle using MERRA and NCEP-reanalysis 2

Abstract: In this study, the global Lorenz atmospheric energy cycle is evaluated using the Modern Era Retrospective analysis for Research and Applications (MERRA) and the National Center for Environmental Prediction and the Department of Energy (NCEP R2) reanalysis datasets over a 30-year period (1979-2008) for the annual, JJA, and DJF means. The energy cycle calculated from the two reanalysis datasets is largely consistent, but the energy cycle determined using the MERRA dataset is more active than that determined fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 14 publications
7
41
0
Order By: Relevance
“…For zones 3 and 4, the reduction in KZ dominated the entire La Niña event; however, the larger reduction in zone 3 was seen between August and December, whereas for zone 4, the major reduction was observed starting from December. According to Kim and Kim [23], KZ production is related to the jet streams in the troposphere and the stratosphere, where there is a maximum production located in the tropics, which corroborates the more significant results in zones 3 e 4.…”
Section: Azsupporting
confidence: 67%
“…For zones 3 and 4, the reduction in KZ dominated the entire La Niña event; however, the larger reduction in zone 3 was seen between August and December, whereas for zone 4, the major reduction was observed starting from December. According to Kim and Kim [23], KZ production is related to the jet streams in the troposphere and the stratosphere, where there is a maximum production located in the tropics, which corroborates the more significant results in zones 3 e 4.…”
Section: Azsupporting
confidence: 67%
“…10). We also note that the gravitational power of precipitation W P has not been explicitly identified in past studies assessing the conversion rates between available potential and kinetic energies in the framework of the Lorenz energy cycle (see, e.g., Kim and Kim, 2013, and references therein).…”
Section: Revisiting the Current Understanding Of The Atmospheric Powementioning
confidence: 96%
“…while published observational estimates range from 2 to 2.5 W m −2 (Kim and Kim, 2013;Schubert and Mitchell, 2013;Huang and McElroy, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…According to Fig. 4c, it can be observed that CK intensified in all areas: by about 6.14% (zone 1), 3.78% (zone 2), 6.31% (zone 3), and 8.88% (zone 4), suggesting a strengthening of the climatological framework, that is, intensification equatorward of the positive contributions of tropospheric jets and stratospheric polar-night jets, as was suggested by Marques et al (2010), and intensification of zonal motion as a result of the poleward transport of momentum by the motion of the eddies, as suggested by Kim and Kim (2013). Analyzing the studied domains, it was noticed that the largest production of CK occurred in the first half of the interval, except in zone 1, where it was observed in December.…”
Section: Energy Conversion Termsmentioning
confidence: 83%
“…Anomalies were predominantly positive and more intense in the period of higher production. According to Kim and Kim (2013), the climatological KZ production is related to the jet streams in the troposphere and the stratosphere, where there is a maximum production between 30°N and 30°S. This suggests that the occurrence of El Niño strengthened the tropospheric and stratospheric jets, leading to a further intensification of the AZ production in the fields located in tropical latitudes (zones 3 and 4).…”
Section: Energy Generation Termsmentioning
confidence: 99%